Refractive Errors in State Junior High School Students in Bandung - Sabila Tasyakur Nikmah; Raden Maula Rifada; Putri Teesa Radhiyanti Santoso (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Uncorrected refractive error is one of the avoidable causes of vision impairment in children and adults. Vision problem in children has been shown to affect their psychological and academic performance. This study aims at identifying and gaining more insights on the characteristic of the refractive errors in state junior high school students in Bandung to avoid uncorrected refractive errors.Methods: A cross-sectional study was conducted in September–November 2015 in state junior high schools in Bandung, West Java, Indonesia. Sample was selected using multistage random sampling technique. Children were examined using tumbling E examination; then students with visual acuity worse than 6/12 underwent Snellen Chart test, refractometry without pupil dilatation, correction with trial lens, then was followed by direct ophthalmoscopy.Results: From a total of 435 children who completed all the examination, 80 children (18.39%) had refractive errors; consisted of 151 eyes (94.38%) with myopia and 9 eyes (5.62%) with astigmatism. Refractive errors were found to be more common in female children (73.7%) than male children (26.3%). Among those with refractive errors, 45 children (56.3%) did not use any corrective glasses before the examination.Conclusions: Routine refractive error test in vision screening examination is needed for students. It is equally important to raise more awareness toward eye disease in community. [AMJ.2016;3(3):545–8]DOI: 10.15850/amj.v3n4.936